Introduction of the concept of social responsibility in the activity of pharmaceutical organizations - N. О. Tkachenko (Zaporozhye State Medical University, 2018)
In respect that the social responsibility of business is employers' voluntary contribution to the development of society, detailed study requires ethical issues, personal motives and other components of the formation of socially responsible behavior of the pharmacy's subjects, taking into account the levels of its formation: personal - collective - public. The aim of the study is to determine the level of understanding of the essence of the concept of "social responsibility" by pharmacy specialists, their views on existing obstacles to the development of social responsibility by pharmaceutical organizations in Ukraine and the motives for introducing social responsibility practices in pharmaceutical activities. Materials and methods. The materials of the study were the results of a sociological survey of pharmacy specialists from several regions of Ukraine. In the course of the work, methods of information retrieval, systematization, comparison, questioning and generalization were used. In the course of the study, the respondents were asked a questionnaire with combined questions regarding the understanding by representatives of practical pharmacy of the concept of "social responsibility of a pharmaceutical organization", obstacles to the development of social responsibility practices by pharmaceutical organizations and the motives for introducing social responsibility in pharmaceutical activities. Conclusions. Most experts in practical pharmacy are familiar with the concept of "social responsibility", but the completeness of its definition is different. Modern specialists do not have a common opinion regarding the manifestation of social responsibility by the pharmaceutical organization. A significant disunity in the initial definitions of the concept is found to necessitate the clarification and dissemination of information on the conceptual foundations of social responsibility with an emphasis on the branch features of its manifestation. It is necessary to develop a unified approach (educational standards) in teaching certain topics of organizational and managerial disciplines at the pre- and post-graduate level. The main obstacles in the development of socially responsible behavior of pharmaceutical organizations are seen by pharmacy specialists in the ineffective support of the state and the absence of a system to encourage such behavior of the pharmaceutical organization, lack of financial opportunities for social investments, and lack of an appropriate legislative framework for social responsibility. An important incentive for widespread implementation of social responsibility practices by pharmaceutical organizations, most respondents consider "awareness and commitment to society." The obtained results testify to the low level of personal (personal) responsibility of specialists, the unformed social competence of modern pharmacists and the desire to shift responsibility to others (the predominance of the external locus of control).